2021
DOI: 10.1038/s41598-021-85555-1
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination strategies against COVID-19 and the diffusion of anti-vaccination views

Abstract: Misinformation is usually adjusted to fit distinct narratives and propagates rapidly through social networks. False beliefs, once adopted, are rarely corrected. Amidst the COVID-19 crisis, pandemic-deniers and people who oppose wearing face masks or quarantine have already been a substantial aspect of the development of the pandemic. With the vaccine for COVID-19, different anti-vaccine narratives are being created and are probably being adopted by large population groups with critical consequences. Assuming f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 51 publications
1
62
0
4
Order By: Relevance
“…A joint statement by WHO et al (2020), regarding the management of COVID-19 pandemic, defined "infodemic", as the overabundance of information, which entailed deliberate attempt to distribute wrong information. Since the vaccinations began, different groups have emerged on social media and made the spreading of misinformation about COVID-19 vaccines and mass immunizations across the globe (Bogart et al, 2021;Paul et al, 2021;Prieto Curiel & González Ramírez, 2021). In January 2020 the WHO has reported that fake news, disinformation, and misinformation threatens COVID-19 vaccines acceptance and COVID-19 vaccination plans across the world.…”
Section: Review Of Related Literature Covid-19 Vaccine "Infodemic" In the Social Mediamentioning
confidence: 99%
“…A joint statement by WHO et al (2020), regarding the management of COVID-19 pandemic, defined "infodemic", as the overabundance of information, which entailed deliberate attempt to distribute wrong information. Since the vaccinations began, different groups have emerged on social media and made the spreading of misinformation about COVID-19 vaccines and mass immunizations across the globe (Bogart et al, 2021;Paul et al, 2021;Prieto Curiel & González Ramírez, 2021). In January 2020 the WHO has reported that fake news, disinformation, and misinformation threatens COVID-19 vaccines acceptance and COVID-19 vaccination plans across the world.…”
Section: Review Of Related Literature Covid-19 Vaccine "Infodemic" In the Social Mediamentioning
confidence: 99%
“…Survey data in the United States indicate that approximately 27% of individuals are reluctant to receive a Covid-19 vaccine, with a majority citing concern surrounding potential adverse effects. 1 …”
mentioning
confidence: 99%
“…Polarisation and the way it emerges is one of the key questions in opinion dynamics models [11]. An increasingly polarised society is observed in attitudes towards the COVID-19 pandemic, views in favour or against a vaccine [12], the consumption of media outlets, opinions on social media and many more. Increased exposure to ideas within an homogeneous community intensifies their tendency to be credulous, whether it is to scientific evidence, unsubstantiated rumours, inconclusive evidence or even fake news.…”
Section: Polarised Opinionsmentioning
confidence: 99%
“…Interactions between individuals are usually modelled on some social structure, such as a network, considering some spatial proximity, or considering some social aspects, such as the level of influence of one individual to others [30]. A long-term, steady distribution of opinions is usually obtained, either as an analytical solution to some differential equations or through simulations, which reveals among others, the formation of opinion clusters, political segregation [31], vaccine hesitancy [12], the use of certain tools [32], the spread of fear of crime more as a result of opinion dynamics than crime itself [29] or even the diffusion of fake news [14].…”
Section: Modelling Opinions and Its Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation